An exploration of the navigational behaviours of people who use wheeled mobility devices in unfamiliar pedestrian environments. (March 2021) - Prescott, Mike; Miller, William C.; Borisoff, Jaimie; Tan, Polly; Garside, Nova; Feick, Robert; Mortenson, W. Ben
Abstract: Purpose: This paper explores the challenges that people who use wheeled mobility devices face navigating unfamiliar pedestrian environments. The intent is to understand their decisions during the planning and travel phases and to compare these decisions and experiences between mobility device users. Methods: Fourteen mobility device users (4 manual wheelchair, 6 power wheelchair, and 4 scooter users) completed surveys that captured data about socio-economic and disability status, mobility device skills and confidence, and wayfinding abilities. As part of a wheeling interview, participants planned trips to three destinations in an unfamiliar urban setting. They wore a GoPro camera affixed to their head and carried a global positioning system device as they wheeled to each destination. During each trip, participants answered questions regarding their decisions and experiences. At the end of each route, participants rated the physical and mental demand of the trip and rated their own performance using the NASA-TLX questionnaire. They also completed wayfinding skills tests of their spatial orientation and ability to estimate distance and slope. Transcripts of the videos were coded and analyzed using interpretive description. Spatial and qualitative data were then uploaded into a geographical information system to identify patterns in decision making and experiences and compare across mobility devices. Results: The findings highlight the complex and dynamic challenges faced by wheeled mobility device users and the implications on their mobility. The findings emphasize the relationship between the individual, the mobility device, and the environment to shape navigational experiences. Manual wheelchair users appeared to struggle more with navigation because accessibility issues diverted their attention away from maintaining orientation and heading. Conclusions: Wheeled mobility device users face challenges navigating unfamiliar environments that make reaching destinations difficult which may deter community participation. Environments that incorporate their diverse and unique requirements should be considered in urban design and research. Highlights: Wheeled mobility device users find navigating unfamiliar environments difficult. Navigation is a balance between wayfinding and accessibility. Navigational experiences differ based on type of mobility device used. Maps and signs need to incorporate the needs of mobility device users.